Probiotic fermentation of polyphenols: potential sources of novel functional foods - Rohit Sharma; Bhawna Diwan; Brij Pal Singh; Saurabh Kulshrestha (Food Production, Processing and Nutrition, 2022)
Abstract Fermented functional food products are among the major segments of food processing industry. Fermentation imparts several characteristic effects on foods including the enhancement of organoleptic characteristics, increased shelf-life, and production of novel health beneficial compounds. However, in addition to macronutrients present in the food, secondary metabolites such as polyphenols are also emerging as suitable fermentable substrates. Despite the traditional antimicrobial view of polyphenols, accumulating research shows that polyphenols exert differential effects on bacterial communities by suppressing the growth of pathogenic microbes while concomitantly promoting the proliferation and survival of probiotic bacteria. Conversely, probiotic bacteria not only survive among polyphenols but also induce their fermentation which often leads to improved bioavailability of polyphenols, production of novel metabolic intermediates, increased polyphenolic content, and thus enhanced functional capacity of the fermented food. In addition, selective fermentation of combinations of polyphenol-rich foods or fortification with polyphenols can result in novel functional foods. The present narrative review specifically explores the potential of polyphenols as fermentable substrates in functional foods. We discuss the emerging bidirectional relationship between polyphenols and probiotic bacteria with an aim at promoting the development of novel functional foods based on the amalgamation of probiotic bacteria and polyphenols. Graphical abstract